In Vitro Polarized Resonance Raman Study of N719 and N719-TBP in Dye Sensitized Solar Cells - Hassing, Søren; Jernshøj, Kit D.; Nguyen, Phuong Tuyet; Lund, Torben (Journal of Technology Innovations in Renewable Energy, 2016)
The working efficiency of dye-sensitized solar cells (DSCs) depends on the long-term stability of the dye itself and on the microscopic structure of the dye-semiconductor interface. Previous experimental studies of DSCs based on ruthenium dye with bipyridine ligands (N719) adsorbed to the TiO2substrate applied FTIR,un-polarized Raman (RS) and un-polarized resonance Raman (RRS) spectroscopy. In the un-polarized RRS studies of N719/TiO2 – DSCs the discussion of the adsorption of N719 was based on the rather weak carbonyl or carboxyl group stretching vibrations and on minor spectral changes of overlapping Raman modes, whereas conclusions about the dye-stability was based on the observation that fresh and aged DSCs had almost identical RRS spectra. In the present paper we address the problems mentioned above, by utilizing the unique property of Raman scattering that the polarization of the scattered light is generally different from the polarization of the laser light. When the excitation is chosen within the visible absorption band of N719 only the skeleton ring-modes in N719 are enhanced and are observed as the most intense bands in the RRS spectra. We demonstrate by experimental results on N719/TiO2 – DSCs that by combining an analysis of the wave number dependent polarization of these modes with the small shifts observed in the visible absorption spectra of adsorbed, non-adsorbed molecules and degradation products new and more reliable information about dye stability and about the adsorption of the dye on TiO2 can be obtained. Furthermore it is found that the polarization fluorescence anisotropy is very different for adsorbed and non-adsorbed dye molecules. This information is automatically obtained when processing the Raman data. The conclusion is that if the polarization properties of the resonance Raman spectra are analyzed instead of just analyzing the minute spectral changes of the (weaker) Raman bands the potential of RRS as an on-site tool for investigation of DSCs can be greatly improved.